2014
DOI: 10.1016/j.midw.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Engaging and supporting fathers to promote breast feeding: A concept analysis

Abstract: Identification of attributes, antecedents, and consequences of father support may assist practitioners to reflect on current working practices and service delivery models, and offer important educational opportunities for the training of student midwives and other health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
90
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 47 publications
10
90
1
3
Order By: Relevance
“…Partners play an important role in the infant feeding decision, and there is a strong association between a partner's positive attitude toward breastfeeding and a mother's intention to breastfeed. 15,[18][19][20] Partners not only influence the decision to breastfeed, but also initiation of the first feeding, duration of breastfeeding, and decision to bottle feed. 17 Moreover, a previous study indicated that mothers feel more capable and confident about breastfeeding when they perceive their partners are supportive by way of verbal encouragement and active involvement in breastfeeding activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Partners play an important role in the infant feeding decision, and there is a strong association between a partner's positive attitude toward breastfeeding and a mother's intention to breastfeed. 15,[18][19][20] Partners not only influence the decision to breastfeed, but also initiation of the first feeding, duration of breastfeeding, and decision to bottle feed. 17 Moreover, a previous study indicated that mothers feel more capable and confident about breastfeeding when they perceive their partners are supportive by way of verbal encouragement and active involvement in breastfeeding activities.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, a previous study indicated that mothers feel more capable and confident about breastfeeding when they perceive their partners are supportive by way of verbal encouragement and active involvement in breastfeeding activities. 18 In the present study, the partner's initial support of breastfeeding was a significant predictor of the employed mother's intention to take advantage of milk expression breaks (OR = 1.43) and to use the lactation room (OR = 1.72) after returning to work and increased the likelihood that the employed mother would continue to breastfeed for the first 6 months (OR = 2.35) and more than 6 months (OR = 1.98) after returning to work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study also suggested that fathers with greater knowledge about breastfeeding had a more positive view of it. (7,8) In Brazil, the nursing profession plays an important role in encouraging health interventions for mothers, with the practice of breastfeeding as a common horizon. Thus, health professionals and fathers can interact, exchange experiences and knowledge for the promotion and protection of women and children's health.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 However, educating and supporting male partner who support the mother is also an important step. 19,20 Studies 21,22 revealed that breastfeeding mothers were less likely to discontinue breastfeeding if it was the preferred feeding method of the father. However, the perception of first time expectant men with regards to infant feeding practices remains unclear and ambiguous and not understood fully by the health professionals.…”
Section: Introductionmentioning
confidence: 99%